SALL1 Modulates CBX4 Stability, Nuclear Bodies, and Regulation of Target Genes - Giordano, Immacolata; Pirone, Lucia; Muratore, Veronica; Landaluze, Eukene; Pérez, Coralia; Lang, Valerie; Garde-Lapido, Elisa; Gonzalez-Lopez, Monika; Barroso-Gomila, Orhi; Vertegaal, Alfred C. O.; Aransay, Ana M.; Rodriguez, Jose Antonio; et al. (Frontiers in Cell and Developmental Biology, 2021)
Development is orchestrated through a complex interplay of multiple transcription factors. The comprehension of this interplay will help us to understand developmental processes. Here we analyze the relationship between two key transcription factors: CBX4, a member of the Polycomb Repressive complex 1 (PRC1), and SALL1, a member of the Spalt-like family with important roles in embryogenesis and limb development. Both proteins localize to nuclear bodies and are modified by the Small Ubiquitin-like Modifier, SUMO. Our results show that CBX4 and SALL1 interact in the nucleoplasm and that increased SALL1 expression reduces ubiquitination of CBX4, enhancing its stability. This is accompanied by an increase in the number and size of CBX4-containing Polycomb bodies, and by a greater repression of CBX4 target genes. Thus, our findings uncover a new way of SALL1-mediated regulation of Polycomb bodies through modulation of CBX4 stability, with consequences in the regulation of its target genes, which could have an impact in cell differentiation and development.